2018
DOI: 10.1016/j.bone.2018.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Vhl deficiency in osteocytes produces high bone mass and hematopoietic defects

Abstract: Tissue oxygen (O) levels vary during development and disease; adaptations to decreased O (hypoxia) are mediated by hypoxia-inducible factor (HIF) transcription factors. HIFs are active in the skeleton, and stabilizing HIF-α isoforms cause high bone mass (HBM) phenotypes. A fundamental limitation of previous studies examining the obligate role for HIF-α isoforms in the skeleton involves the persistence of gene deletion as osteolineage cells differentiate into osteocytes. Because osteocytes orchestrate skeletal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 51 publications
7
33
0
Order By: Relevance
“…29 Studies showed that loss of VHL significantly promoted angiogenesis via enhancing HIF-1α expression. 30 In our further WB results, the VHL gene was less expressed in the HP Mg group at three, six, and nine weeks postoperatively, and was lowest at the sixth week. In summary, combined with the results of all previous trials, we propose a mechanism hypothesis that magnesium promotes osteogenesis and calcification of distracted osteogenic new bone.…”
Section: Discussionmentioning
confidence: 59%
“…29 Studies showed that loss of VHL significantly promoted angiogenesis via enhancing HIF-1α expression. 30 In our further WB results, the VHL gene was less expressed in the HP Mg group at three, six, and nine weeks postoperatively, and was lowest at the sixth week. In summary, combined with the results of all previous trials, we propose a mechanism hypothesis that magnesium promotes osteogenesis and calcification of distracted osteogenic new bone.…”
Section: Discussionmentioning
confidence: 59%
“…Nevertheless, inappropriate HIF-1α signaling resulted in collagen overmodification and skeletal dysplasia (Stegen et al 2019), suggesting the complicated role of HIF-1α in endochondral osteogenesis. HIF-1α was considered to be required for osteoclast activation in postmenopausal osteoporosis (Miyauchi et al 2013; Loots et al 2018; Stegen et al 2018). However, the unique function of osteoclasts in condylar development was poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…After euthanasia, femora were stripped of soft‐tissue, fixed in 3.7% formaldehyde in phosphate‐buffered saline for 48 h at 4°C, then transferred to 70% ethanol in water and stored at 4°C; later, femora were scanned at 55 kVp, 145 mA, with 6 μm voxel size (Scanco Medical μCT 35, Brüttisellen, Switzerland) in the manner of Loots et al Tissue mineral density distribution (TMDD) within mid‐diaphyseal cortical bone from sham and Abx‐treated mice was obtained by distributing voxels into 100 evenly spaced bins (410–1,500 mg HA/cm 3 ). Mean calcium content (Ca MEAN ), peak calcium content (Ca PEAK ), and width at half‐maximum (Ca WIDTH ) were calculated in the manner of Borah et al Briefly, Ca MEAN reflects the average mineralization of the whole bone sample, Ca PEAK indicates the most frequently occurring calcium concentration, and Ca WIDTH is the width of the calcium distribution at its half peak height.…”
Section: Methodsmentioning
confidence: 99%